Respuesta :
I'm assuming you mean [tex]f(x) = (e^x + 5x)^2[/tex], not [tex]f(x) = (e x + 5x)2[/tex], like your prompt suggests.
First, let's figure out what rule we can use. A likely noticeable one is the Power Rule, which says the following:
[tex]\dfrac{d}{dx} [u^a] = a(u)^{a-1} du[/tex]
Applying this, we can solve for the derivative:
[tex]f'(x) = 2(e^x + 5x) (e^x + 5)[/tex]
- Apply the Power Rule
While you can simplify the expression to your liking, I believe that this form is not overly complex and will thus leave it as is.
Thus, our answer is:
[tex]f'(x) = \boxed{2 (e^x + 5x)(e^x + 5)}[/tex]